(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2015)
In her thorough essay, Maria Silvia Da Re discusses the French and Italian tradition of the Sonnets, strictly linked, especially considering the point of view of the taste. Notwithstanding the inherent ambiguity of this subject, about which several parameters are here made explicit, the various ‘standards’ of taste turn out to be a sort of litmus paper of the values conveyed by translation, not necessarily or straightforwardly related to the selected style. But then, which style does really belong to the shaping of poetic translation?